OPTIMAL SOLUTIONS FOR IMPROVING JOB SATISFACTION AMONG HIGH SCHOOL TEACHERS ON P3K CONTRACTS - Halimatusha’diah Halimatusha’diah; Bibin Rubini; Hendarman Hendarman (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to identify the optimal solution from among the available options, given the limitations of management resources. The research methodology employed a quantitative study, with the sample size calculated using Taro Yamane’s formula, resulting in a sample of 113 P3K teachers teaching at state senior secondary schools in Karawang Regency. The instrument used in this study was a questionnaire covering each research variable, which had previously been validated. To determine the optimal solution, the SITOREM analysis was used, based on four assessment criteria, namely: 1) cost, 2) benefit, 3) urgency, and 4) importance. The assessment was carried out by experts in their respective fields of educational management. The research results indicate that there are three indicators that require improvement, namely fair/appropriate remuneration, indirect financial benefits, and the tangible benefits of the remuneration received. As for the indicators to be retained or developed, there are 17, namely: working environment, recognition, opportunities for advancement, feelings towards the job itself, direct financial rewards, non-financial rewards, acceptance of the organisational environment, a sense of identification with the organisation, belief in the organisation’s values and objectives, involvement in organisational tasks, a strong desire to remain part of the organisation, career fairness, self-development, career clarity, attention from supervisors, the presence of goals to be achieved, perseverance in achieving goals, and the intensity of effort expended. The implications of the research findings are that there is efficiency in the management of human resources.